A Positive Psychology Intervention Among Long‐Term Unemployed People and Its Effects on Psychological Distress and Well‐Being. Issue 2 (2nd June 2014) - Dambrun, Michaël; Dubuy, Anne‐Laure
<x xml:space="preserve">Abstract</x> The present study aims to examine the effect of a positive psychology intervention (PPI) on a population of long‐term unemployed people. All were members of an association of employment assistance. An opportunity was offered to participate in a PPI. Twelve participants accepted (treatment condition). The remaining participants constituted the control group. Participants of the treatment condition were asked to complete 5 positive psychology exercises during 2 weeks. Participants of the control condition participated as usual in sessions to help their job search. Results indicate that PPI significantly decreases psychological distress (e.g., depression, anxiety) and significantly increases well‐being (e.g., life satisfaction, self‐esteem).